Mismatch between antenatal care attendance and institutional delivery in south Ethiopia: A multilevel analysis. Issue 3 (20th March 2019) - Asefa, Anteneh; Gebremedhin, Samson; Messele, Tamiru; Letamo, Yohannes; Shibru, Endashaw; Alano, Abraham; Morgan, Alison; Kermode, Michelle
Abstract : Objectives: Uptake of maternal health services remains suboptimal in Ethiopia. Significant proportions of antenatal care attendees give birth at home. This study was conducted to identify the predictors of non-institutional delivery among women who received antenatal care in the Southern Nations Nationalities and Peoples Region, Ethiopia. Design: A community-based cross-sectional survey was conducted among women who delivered in the year preceding the survey and who had at least one antenatal visit. Multistage cluster sampling was deployed to select 2390 women from all administrative zones of the region. A mixed-effects multivariable logistic regression analysis was performed to assess the predictors of non-institutional delivery; adjusted ORs (AOR) with 95% CIs are reported. Results: The proportion of non-institutional deliveries among participants was 62.2% (95% CI 60.2% to 64.2%). Previous experience of short and simple labour (46.9%) and uncomplicated home birth (42.9%), night-time labour (29.7%), absence of pregnancy-related problem (18.8%) and perceived providers poor reception of women (17.8%) were the main reasons to have non-institutional delivery. Attending secondary school and above (AOR=0.51; 95% CI 0.30 to 0.85), being a government employee (AOR=0.27; 95% CI 0.10 to 0.78) and woman's autonomy in healthcare utilisation decision making (AOR=0.51; 95% CI 0.33 to 0.79) were among the independent predictors negatively associated with non-institutional delivery. On the other hand, unplanned pregnancy (AOR=1.67; 95% CI 1.16 to 2.42), not experiencing any health problem during pregnancy (AOR=8.1; 95% CI 3.12 to 24.62), not perceiving the risks associated with home delivery (AOR=6.64; 95% CI 4.35 to 10.14) were the independent predictors positively associated with non-institutional delivery. Conclusions: There is a missed opportunity among women attending antenatal care in southern Ethiopia. Further health system innovations that help to bridge the gap between antenatal care attendance and institutional delivery are highly recommended.